Maintenance of air conditioning / Muhamad Fauzi Hashim - Hashim, Muhamad Fauzi (Universiti Teknologi Mara, Perak, 2016)
Perbadanan Kemajuan Negeri Melaka (PKNM) was established on 30 April 1971 under the enactment of the development of the state which plays a major role in propelling the state of Malacca through continuous involvement in various economics sectors including industrial, small and medium industry, trade and real estate development. In line with the new economics policy objectives, especially to eradicate poverty and restructure society, PKNM also responsible for promoting indigenous participation and more active in economics sectors inline with efforts to create Bumiputera commercial and industrial community more sustainable and viable. Generally the function and role of the PKNM based on two things, namely furthering economics sectors and strengthen the socio-economics position to prevent the momentum of success state of Malacca as an advanced state of dynamic and progressive.